New Testament Theology Re-Loaded: Integrating Biblical Theology and Christian Origins - Bird, Michael (Tyndale bulletin, 2009)
This study examines the problem of balancing the historical and theological components of New Testament Theology. It presents a critique of both Biblical Theology and Christian Origins and finally argues for a ‘Theology of the New Covenant’ where theology emerges out of the interface of canon and community.